Perancangan Fasilitas Publik Di Tropical City Garden, Pusat Informasi Dan Konservasi Bunga Tropis Di Surabaya Menggunakan Material Rotan - Nivella Antonnios (Intra, 2017)
Rattan is one of the natural products that is widely used in many industries. Indonesia is one of the countries that produces rattan. The government regulation stipulated in the Decree of the Minister of Trade No. 35 / M-DAG / PER / 11/2011 on banning the export of raw materials made rattan industry in Indonesia has decreased. Rattan which is the original material of Indonesia, should have the opportunity and freedom to control world’s rattan markets, especially funiture. One way to improve Indonesia's rattan industry is to allow designers to contribute creating rattan furniture designs that enhance the rattan industry in Indonesia, and then introduce their designs to the public through public places such as Tropical City Garden. The method used to design is design thinking method that is consist of problem solving process, field collection, literature, typology, programming analysis, synthetics, schematic design, preparation, and the design manifestation. . The purpose of this arrangement is to create furniture that can enhance the rattan image and accommodate visitor’s activity at Tropical City Garden.